Surveillance of antimicrobial resistance among clinical isolates recovered from a tertiary care hospital in Al Qassim, Saudi Arabia - Said, Kamaleldin B; Al-Jarbou, Ahmed N; Alrouji, Mohammed; Al-harbi, Hajed O (International Journal of Health Sciences, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–> Background: The emergences of antimicrobial-resistances have become an important issue in global healthcares. Limitations in surveying hinder the actual estimates of resistance in many countries. The aim: the present study was designed to retrospectically survey antimicrobial susceptibility for resistance profiling of dominant pathogens in a tertiary-care center in Buraidah, Saudi Arabia from January-2011 to December-2011. Materials and Methods: the design was cross-sectional and spanned records of a 1000 bacterial non-related isolates. Antibiograms were based on the 2012 Clinical and Laboratory Standards Institute guidelines. Results showed that Staphylococcus aureus, Acinetobacter baumannii, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus epidermidis, and Escherichia coli, were the most resistant. All isolates of S. aureus, S. epidermidis, and Staphylococcus haemolyticus, were resistant to penicillin (100%), and oxacillin with 52%, 75%, and 82%, respectively. Interestingly, an increasing trend of resistance-pattern was seen for the three species against gentamicin 26%, 50%, 68% ciprofloxacin 22%, 50%, 68%, tetracycline 30%, 44%, 27%, erythromycin 26%, 64%, 73%,Â and clindamycin 20%, 47%, 50% suggesting potential between- species transfer of resistances. Acinetobacter baumannii was resistances to all antibiotics tested including ciprofloxacin (90%), ceftazidime (89%), cefepime (67%), Trimethoprim/sulfamethoxazole (66%), amikacin (63%), gentamicin (51%), tetracycline (43%), piperacillin-tazobactam (42%), and imipenem (9%). A similar pattern was seen by P. aeruginosa. Furthermore, a typical pattern of resistance in K. pneumoniae carbapenemaseâ€“producing organisms was observed. Conclusion: we have shown staphylococci, Acinetobacter baumannii, Pseudomonas aeruginosa, and enteric bacteria were the most resistant species in this region. Key Words:Â Antimicrobial-Resistance, nosocomial-pathogens, AST-surveillance program, infection control <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>